Prototype Application for Data Processing Teacher Performance Assessment at Christian Elementary School Imanuel Nunu - Paula Aneke Ruung; Esther Sanda Manapa; Valian Yoga Pudya Ardhana; Hoxy R Taluay; Eliyah A M Sampetoding (STMIK Budi Darma, 2022)
The Performance every employee appraisal is a method used to assess the work performance of an employee whether he or she has achieved the work target assigned.Teacher performance appraisal at Imanuel Nunu Christian Elementary School is currently still being carried out manually in the sense that the preparation of employee performance appraisal reports still uses word processing applications (Microsoft word and excel) resulting in inefficient and ineffective time and a greater risk of data loss. The purpose that the authors take from this research is to build a Data Processing Application for Teacher Performance Assessment at Imanuel Nunu Christian Elementary School using computerized visual basic 6.0. The Teacher Performance Assessment that was made was a Data Processing Application for Teacher Performance Assessment at Imanuel Nunu Christian Elementary School by using the Visual Basic 6.0 programming language and Microsoft Office Access as databases. The results obtained are a prototype of the teacher performance assessment report at the Imanuel Nunu Christian Elementary School